PENGARUH POLA KEPEMIMIPINAN KEPALA SEKOLAH TERHADAP KEPUASAN KERJA GURU SD DI KECAMATAN GANTIWARNO KABUPATEN KLATEN - Sri Suwartini; Isna Rahmawati; Putri Zudhah Ferryka; Sabar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the leadership of principals on the job satisfaction of elementary school teachers in Gantiwarno Klaten. The type of study used was ex-post facto because the study only presented data on events that have already taken place and been had by the respondents without giving treatment or manipulation of the studied variables. The subject and population selected from the study involved 70 teachers of five elementary schools in Gantiwarno Klaten. Data were collected by using a questionnaire technique. The results indicated that the leadership of the principal together contributed 24.1% to the improvement of job satisfaction of elementary school teachers in Gantiwarno. The principal's leadership did not have a significant effect on the job satisfaction of elementary school teachers since (1) there was no interest or high encouragement of the principal’s leadership in trusting the respective duties of the teachers, staff, and students excitedly. In addition, (2) The principal did not provide guidance, or direction to the teachers, staff, and students, and give the encouragement, spur, and stand up as a leader and inspirator in order to acquire the school achievement.